The Temettok Tradition at Walimatul Ursy According to Aceh Ulama and Traditional Assembly (MAA): (A Case Study in Aceh Singkil District) - Syam, Syafruddin; Syahputra, Akmaluddin; Dasri, Dasri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The temettok tradition in the context of law is basically permissible, but in its journey, this shift in tradition has undergone significant changes, especially in the essence of this tradition itself, which is a tradition built on the principles of ta'awun and mutual cooperation, but shifts to economic values ​​that are demanded its citizens to bear expenses which in principle were like debt. This research aimed to find out how the Temettok tradition at walimatul ursy according to Aceh Ulama Traditional Assembly (MAA). The approach used in this research was to use a qualitative approach. The results of this research indicated that first, The tradition of recording Temettok money when the walimatul ursy in Aceh Singkil Regency had two percentages, the first is the Cinendang river, which was estimated to have existed since 1985. The two Sungkhaya rivers were thought to have existed since 1956. So, this Temettok tradition held at the time of the walimah to be precise on the last day. Second, The Temettok tradition, in the view of Aceh Ulama and Traditional Assembly (MAA), allowed this tradition by reason of the principle of fiqh “a custom can be made into law”, besides that the Temettok tradition was also in the form of a grant, not a debt, because if a debt was owed, the law was haram, because tradition might not conflict with Islamic law. Thret, After analyzing more deeply based on the verses of the Qur'an and the hadith of the Prophet Muhammad SAW, that the Temettok tradition was classified as ‘urf Sahih, because, this urf applied in general, it did not contradict Islamic law, the gift was in the form of a grant. So apart from that, if it was seen from the social side, the Temettok tradition at the time the walimah put forward help, strengthened ties, strengthened ukhuwah and the Temettok tradition was well known in the community.